What does Paris mean for Africa? An integrated assessment analysis of the effects of the Paris Agreement on African economies - Kelly C. De Bruin; Victoria Ayuba (The Economic and Social Research Institute (ESRI), 2020)
Climate change is considered the biggest environmental challenge facing the world. The expected concomitant economic impacts of climate change are substantial, where the African continent is expected to be particularly vulnerable. Research is needed to support the development of sound climate policies in Africa. This paper develops a new Integrated Assessment Model -AD-AFRICA- which allows a comprehensive analysis of climate change impacts and adaptation in Africa. The AD-AFRICA model divides Africa into five regions and includes seven specific climate change impacts. The effects of the Paris agreement Intended Nationally Determined Contributions (INDCs) and the below 2 degrees target are investigated. The results show that though the INDCs reduce impacts, reaching the goal of the agreement will further reduce impacts by almost 1.6 % of GDP (588,731 US Billion). This highlights the importance of re-examining the level of INDCs. Furthermore, our results show that health and tourism impacts are highest and that different regions in Africa are more vulnerable to different climate change impacts depending on their level of development and regional characteristics. Finally, the withdrawal of the US from the Paris Agreement would result in an additional climate change burden of around 87 US Billions to Africa.
Keywords: 330